Enhancement of ZnO Dye-Sensitized Solar Cell Performance by Modifying Photoelectrode Using Two-Steps Coating-Etching Process - Sutthipoj Sutthana (2018)
© 2015 The Authors. Published by Elsevier Ltd. ZnO photoelectrodes modified by two-steps coating-etching process with chemical wet etchants for dye-sensitized solar cell were investigated. The ZnO films were coated on a fluorine-doped tin oxide glass substrate and etched by mixed acid solution of HCl:HNO3:distilled water, washed, and thermally treated for the first step. The second step, films coating process was repeated and etched by base solution of diluted NH4OH in distilled water. Surface morphologies of unmodified and modified ZnO films look similar DSSCs with modified photoelectrodes showed efficiency enhancement with maximum power conversion efficiency of 2.29%. From EIS analysis, it was suggested that the fill factor plays an important role on enhancement of power conversion efficiency. The fill factor increased due to the formation of pores structure in the photoelectrodes during etching process.